L'Académie de Lausanne entre Humanisme et Réforme (ca. 1537-1560) - Crousaz, Karine (Education and Society in the Middle Ages and Renaissance, 2011)
Based on a vast body of archival sources, this book examines the development and the operations of the Lausanne Academy, the first Protestant Academy of Higher Education created in a French-speaking territory, and an essential milestone in the history of European education. Readership: All those interested in the history of education, the history of universities, intellectual history, Swiss history, the history of the Reformation and the history of Renaissance humanism.